Usability and Impact of the Web-Based Dementia Foundations Educational Program in Personal Support Workers (PSWs), PSW Trainees, and Care Companions: Quasi-Experimental Study - Levinson, Anthony J; Ayers, Stephanie; Clark, Sandra; Gerantonis, Patricia; Schneeberg, Amy; Sztramko, Richard (JMIR aging, 2025)
Personal support workers (PSWs) are often expected to provide ongoing support for complex conditions and have identified an increased need for training in several areas, including dementia and mental health. Web-based interventions may be helpful complements to traditional in-person continuing education and training, but their effectiveness must be explored further. This study's objective was to evaluate the usability, usefulness, satisfaction with, and effectiveness of the web-based Dementia Foundations Program among unregulated care providers who provide care to persons living with dementia or are in training. A cohort of 50 PSWs, PSW trainees, and paid care companions from 3 recruitment sites were invited to access the Dementia Foundations Program, a 4-hour self-paced web-based program composed of 4 courses, for up to 6 weeks. Usability, usefulness, and satisfaction were assessed using surveys after each course and following the program. Dementia knowledge and attitudes were measured using the Dementia Knowledge Assessment Scale and the Dementia Attitudes Scale, with differences between baseline and postprogram scores analyzed using repeated measures ANOVA. Participants reported high levels of satisfaction with the program. Of the 50 participants, 46 (92%) agreed that the web-based training met their expectations, 47 (94%) agreed that the training covered a broad range of topics and was not missing any important content, and 49 (98%) agreed that the web-based training would benefit them. There was a significant postprogram improvement in dementia knowledge as measured by the Dementia Knowledge Assessment Scale, with an average 30% improvement across all cohorts. Dementia Attitudes Scale scores were also significantly improved postprogram across all cohorts. This pilot study in PSWs, PSW trainees, and unregulated care companions demonstrated high satisfaction levels with the web-based Dementia Foundations Program. There were substantial improvements in knowledge and small improvements in attitudes for participants, and it was perceived as a useful tool that complemented their existing education and training. The Dementia Foundations Program is a user-friendly and effective e-learning program, which can be conveniently scaled and spread to enhance unregulated care provider dementia education.